2009
DOI: 10.1038/nn.2335
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic modulation of odor input to the mammalian olfactory bulb

Abstract: Centrifugal serotonergic fibers innervate the olfactory bulb, but the importance of these projections for olfactory processing is unclear. We examined serotonergic modulation of sensory input to olfactory glomeruli using mice that express synaptopHluorin in olfactory receptor neurons (ORN). Odor-evoked synaptic input to glomeruli was attenuated by increased serotonin signaling through serotonin 2C (5-HT2C) receptors and amplified by decreased serotonergic activity. Intravital multiphoton calcium imaging reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
197
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(206 citation statements)
references
References 46 publications
6
197
1
Order By: Relevance
“…Although the effect of anesthesia on the peripheral inputs is negligible (42), it is more significant for the central processes (1,19). The OB receives modulatory inputs from several nuclei (16)(17)(18)43) and heavy feedback inputs from many cortices (11,43,44). Because multiple receptor types of these pathways spread over the OB, the effect of anesthesia on modulatory inputs is difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of anesthesia on the peripheral inputs is negligible (42), it is more significant for the central processes (1,19). The OB receives modulatory inputs from several nuclei (16)(17)(18)43) and heavy feedback inputs from many cortices (11,43,44). Because multiple receptor types of these pathways spread over the OB, the effect of anesthesia on modulatory inputs is difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
“…The information is mainly processed in the external plexiform layer that contains a dense dendrodendritic network formed between the secondary dendrites of the mitral/tufted (M/T) cells, whose somas are located in the MCL, and the dendrites of granular cells, whose somas are located in the GCL, then sent to higher olfactory centers by M/T cells (11,14,15). Under given conditions, the representation and process of the olfactory information in the OB and the regulation of OB activity by the other brain regions have been extensively studied, and have greatly advanced our understanding of the olfactory system (6,(16)(17)(18). However, how the OB processes, represents, and transmits information of the same olfactory stimulus in different brain states has not been systematically investigated (19)(20)(21).…”
mentioning
confidence: 99%
“…Ultimately, these results imply that stronger and/or more synchronous inputs from cortex and thalamus are necessary to initiate action potentials in MSNs during periods of histaminergic activity. Such negative modulation of excitatory inputs is reminiscent of gain control used by sensory systems (Petzold et al, 2009) to keep the postsynaptic response within a normal dynamic range and preventing input saturation.…”
Section: Histaminergic Modulation Of Excitatory Inputsmentioning
confidence: 99%
“…Injection of a specific serotonergic neurotoxin in adult rats results in reduced olfactory discrimination, and depletion of 5-HT fibres in rat pups causes a failure in the development of odour preference (Moriizumi et al, 1994;McLean et al, 1993). Petzold et al (2009) suggested that the serotonergic system regulates odour input in the OB. Glomerular activation after odour stimulation is attenuated by 5-HT 2C receptor activation and amplified by 5-HT 2C receptor inhibition (Petzold et al, 2009), indicating a prominent role of serotonin in the initial steps of olfactory processing.…”
Section: Monoamines: Noradrenaline Serotoninmentioning
confidence: 99%
“…Petzold et al (2009) suggested that the serotonergic system regulates odour input in the OB. Glomerular activation after odour stimulation is attenuated by 5-HT 2C receptor activation and amplified by 5-HT 2C receptor inhibition (Petzold et al, 2009), indicating a prominent role of serotonin in the initial steps of olfactory processing. Whether serotonin-mediated effects involve also regulation of newborn olfactory interneurons seems to be unlikely.…”
Section: Monoamines: Noradrenaline Serotoninmentioning
confidence: 99%